2022
DOI: 10.1055/s-0042-1751222
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Management of Colorectal Vascular Malformation in Children: A Retrospective Study of 23 Cases

Abstract: Introduction The objective of this study is to summarize the clinical characteristics and management of rare diseases of colorectal vascular malformation (CRVM) in children. Methods We retrospectively analyzed the clinical data of CRVM patients admitted to the Children's Hospital of Fudan University from 2004 to 2019. Results A total of 23 cases (16 males, 7 females) were enrolled. The median age of symptom onset was 1.4 years. Hematochezia and anemia were cardinal symptoms. Fourteen patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It has been shown that DBE is an effective tool to diagnose MD with a positive rate of 68.1 [ 231 ]. According to clinical features and accessibility, imaging such as MRI and CT is complementary to endoscopy in diagnosing MD [ 232 ]. DAE, despite being invasive, is often used as a second-line diagnostic tool in patients with suspected small-bowel hemorrhage, and has shown high sensitivity and specificity for MD [ 218 ].…”
Section: Imaging Of Gastrointestinal Diseasesmentioning
confidence: 99%
“…It has been shown that DBE is an effective tool to diagnose MD with a positive rate of 68.1 [ 231 ]. According to clinical features and accessibility, imaging such as MRI and CT is complementary to endoscopy in diagnosing MD [ 232 ]. DAE, despite being invasive, is often used as a second-line diagnostic tool in patients with suspected small-bowel hemorrhage, and has shown high sensitivity and specificity for MD [ 218 ].…”
Section: Imaging Of Gastrointestinal Diseasesmentioning
confidence: 99%